Desenvolvimento de uma desfribadeira para obtenção da fibra da folha do abacaxi - Aquino, Marcos Silva de (2006)
In 1998 the first decorticator was developed in the Textile Engineering Laboratory and patented for the purpose of extracting fibres from pineapple leaves, with the financial help from CNPq and BNB. The objective of the present work was to develop an automatic decorticator different from the first one with a semiautomatic system of decortication with automatic feeding of the leaves and collection of the extracted fibres. The system is started through a command system that passes information to two engines, one for starting the beater cylinder and the other for the feeding of the leaves as well as the extraction of the decorticated fibres automatically. This in turn introduces the leaves between a knife and a beater cylinder with twenty blades (the previous one had only 8 blades). These blades are supported by equidistant flanges with a central transmission axis that would help in increasing the number of beatings of the leaves. In the present system the operator has to place the leaves on the rotating endless feeding belt and collect the extracted leaves that are being carried out through another endless belt. The pulp resulted form the extraction is collected in a tray through a collector. The feeding of the leaves as well as the extraction of the fibres is controlled automatically by varying the velocity of the cylinders. The semi-automatic decorticator basically composed of a chassis made out of iron bars (profile L) with 200cm length, 91 cm of height 68 cm of width. The decorticator weighs around 300Kg. It was observed that the increase in the number of blades from 8 to twenty in the beater cylinder reduced the turbulence inside the decorticator, which helped to improve the removal of the fibres without any problems as well as the quality of the fibres. From the studies carried out, from each leaf 2,8 to 4,5% of fibres can be extracted. This gives around 4 to 5 tons of fibres per hectare, which is more than that of cotton production per hectare. This quantity with no doubt could generate jobs to the people not only on the production of the fibres but also on their application in different areas